Movement patterns of an endangered fishery species, Lithognathus lithognathus (Sparidae), and the role of no-take marine protected areas as a management tool. Issue 4 (1st December 2017) - Bennett, RH; Cowley, PD; Childs, A-R; Attwood, CG; Swart, L; Næsje, TF
Abstract : Understanding movement behaviour is essential for effective management of fishery species. Dart tags were used to study coastal movement patterns of white steenbras Lithognathus lithognathus, an overexploited seabream (Sparidae) in South Africa. In total, 6 962 fish (190–1 080 mm fork length) were tagged throughout the species' distributional range, in four long-term fish-tagging programmes. The predominant behaviour recorded was residency, with relatively short-ranging movements. More than 60% of the 351 recaptured fish were recaptured within 1 km of their tagging site, some of which were at liberty in excess of three years. Most of the juveniles (93.9%), subadults (71.7%) and adults (64.0%) were recaptured within 10 km. Occasional long-distance movements of up to 800 km were recorded. Recapture distances were positively, but weakly, correlated with fish fork length ( n = 257 fish measured at recapture; r 2 = 0.166, p < 0.001). Low levels of connectivity among coastal areas suggest that large-scale annual spawning migrations, as previously hypothesised for this species, are unlikely, which raises the possibility of multiple spawning sites. Seventy-seven percent of L. lithognathus tagged within three marine protected areas (MPAs) were recaptured within the same MPA, suggesting that area closures provide protection for L. lithognathus through the post-estuarine juvenile, subadult and adult life stages. We confirm that the country's current network of coastal MPAs plays a vital role in sustaining this species, and suggest that additional closures, or otherwise substantial reductions in catch rates, are necessary for the species' recovery.